DNA‐Targeted NO Release Photoregulated by Green Light. Issue 60 (28th September 2020) - Parisi, Cristina; Fraix, Aurore; Guglielmo, Stefano; Spyrakis, Francesca; Rolando, Barbara; Lazzarato, Loretta; Fruttero, Roberta; Gasco, Alberto; Sortino, Salvatore
Abstract: A novel molecular hybrid has been designed and synthesized in which acridine orange (AO) is covalently linked to an N ‐nitrosoaniline derivative through an alkyl spacer. Photoexcitation of the AO antenna with the highly biocompatible green light results in intense fluorescence emission and triggers NO detachment from the N ‐nitroso appendage via an intramolecular electron transfer. The presence of the AO moiety encourages the binding with DNA through both external and partially intercalative fashions, depending on the DNA:molecular hybrid molar ratio. Importantly, this dual‐mode binding interaction with the biopolymer does not preclude the NO photoreleasing performances of the molecular hybrid, permitting NO to be photogenerated nearby DNA with an efficiency similar to that of the free molecule. These properties make the presented compound an intriguing candidate for fundamental and potential applicative research studies where NO delivery in the DNA proximity precisely regulated by harmless green light is required. Abstract : A novel fluorescent molecular hybrid based on acridine orange antenna binds DNA in a double fashion and releases nitric oxide under the exclusive excitation of green light.